ANALISIS PENGGUNAAN TAGAR #PERCUMALAPORPOLISI DAN DALAM FUNGSI COMPUTER MEDIATED COMMUNICATION DI INSTAGRAM - SUSANTO, MOCHAMAD FARID (Journal Communication Specialist, 2025)
Known as computer-mediated communication, computer-mediated digital interaction or communication allows everyone to interact without ever meeting in person. This is based on a recent survey conducted by the Indonesian Internet Service Users Association from January 11 to February 24, 2022, and involved 7,568 respondents in various parts of Indonesia. Among them, Instagram is one of the most used social media. Instagram holds the record for the most used social media after WhatsApp. Social media hashtags are useful for grouping content in such a way that it’s easy to search. The #2019GantiPresiden hashtag is an introductory content that covers Joko Widodo’s image as Indonesia’s president, while #jokowi2period claims the opposite, namely that he deserves to be the next president. The hashtags mark content related to campaigns or public relations to prevent the spread of viruses in homes. The history of the initial emergence of the hashtag #PercumaLaporPolisi occurred on October 6 2021, the hashtag #Percumalaporpolisi became a trending topic on Twitter social media. This research is qualitative in nature, namely the social reality being studied (Mamik, 2015). Therefore, in this study the phenomena are described as they are, and then discussed according to the ideas of this research, without seeing what should have happened. This research examines the hashtags #percumalaporpolisi as a means of communication between content creators and content recipients. This research is descriptive in nature, that is, it examines a phenomenon and describes it in words (Rusandi & Rusli, 2021). The information collected is not in the form of numbers but in the form of words or pictures (Moleong, 2010). Therefore, content related to police performance cases that appear on the Instagram social network that is searched for with the hashtags #free reportorpolisi and #1hari1oknum are collected and described using the hashtag theory (#) as a CMC tool.